Investigating the preliminary adaptation of plants to different levels of salinity (Case study: Dust hotspot No 4, Khuzestan) - Maasoumeh Movaghari; bijan khalili moghadam; Leila Khalasi Ahvazi; Ashkan Yousefi; Amin Zorati Pour; Masoumeh Forouzani; seyed ata Siadat; zeinab Hazbavi; Mohammad Hossein Salehe Shooshtari (مدیریت بیابان)
Extended Abstract IntroductionKhuzestan province is one of the main hotspots of dust generation in Iran due to special geomorphological and climatic conditions, which expose it to the highest amount of dust. The dust hotspots of Khuzestan are located in seven areas with an area of 350,000 hectares, among them. The dust hotspot in the south and southeast of Ahvaz (dust hotspot No. 4) is the largest and one of the most critical dust hotspots in the province. Rehabilitation projects prioritize this location because of its salinity, alkalinity, and severe climate conditions. Identification of plant species is the first step in rehabilitating these ecosystems that can withstand environmental stress, decrease ecosystem interference, and provide more ecosystem services to local communities while protecting water and soil resources. The above goals can be achieved by planting native species, which also increases the chances of species adaptation (establishment and survival). Numerous studies have been conducted to determine the most suitable species for land reclamation. A researcher is investigating the possibility of planting, establishing, and supplying fodder for four species of halophytes in the Miqan Arak desert. The study's findings indicate that Halimion verrucifera, a native species in the region, is more advantageous in terms of fodder production and palatability. Therefore, cultivation of this species is recommended in this area. In another study, researchers evaluated salt-resistant wood species for land reclamation in Australia. This study focuses on comparing several species from Eucalyptus, Melaleuca, Acacia, and Casuarina in both greenhouse and field conditions. They suggested two species, E. camaldulensis and E. occidentalis, for further and supplementary investigations. Despite the extensive plantings in the Khuzestan dust hotspots in recent years, no research has been conducted to choose the suitable species for land reclamation in these areas. On the other hand dominant species in these projects was Prosopis.juliflora, which is a non-native species. The objective of the current study is to evaluate the establishment, survival, and growth characteristics of Pr. juliflora (Sw.) with 5 species: Tamarix aphylla (L.), Tamarix passerinoides (Delile ex Desv.), Lycium depressum (L.), Eucalyptus camaldulensis (Dehnh.) Seidlitzia rosmarinus (Bunge ex Boiss). Material and MethodsDust hotspot No 4, Khuzestan is located approximately 25 km southeast of Ahvaz city and along the Ahvaz-Mahshahr highway, at a geographic coordinate system of 48° 47' to 49° 17' east longitude and 30° 15' to 31° 15' north latitude. This region experiences an average rainfall of 218 mm, a maximum temperature of 27.7 degrees Celsius, and a minimum temperature of 24.4 degrees Celsius. The climate of the region is classified as hyper-arid by the de Martonne climate classification method. After selecting the plant species, three levels of salinity were selected: high (61-105 dS/m) (Zone 1), medium (16-60 dS/m) (Zone 2), and low (0-15 dS/m) (Zone 3) with an area of about 30560 m2. 288 seedlings were planted in each salinity level and 864 in total number of seedlings = 3 (different salinity levels) × 6 (different species) × 48 (repetition) (four farrow and 12 repetitions in each farrow). Seedlings were prepared from Dezful, Hamidiyeh, Ramhormoz and Bagh Malik Plant nurseries. Planting distances and dimensions of holes for four species of T.passerinoides, T.aphylla, Pr.juliflora and Eu.camaldulensis were determined as 5 meters and 50x50x50 cm, respectively, and for two species Se.rosmarinus and Ly.depressum, 3 meters and 30x30x30 cm, respectively. After planting the seedlings, the first watering was carried out immediately with an average of 20 liters per seedling hole. Then, watering was done every 10 days until the dry season, and every week during it. Until the seedlings were fully established, livestock was prevented from entering the planted areas with the help of local forces. Measurements were taken after planting the seedlings, including canopy cover (large and small diameter), basal cover, and height of seedlings for every treatment, and replicates three times immediately after planting, six months after planting, and one year after planting. The survival rates were recorded at intervals of six months and one year after planting. The investigated characteristics at different salinity levels were compared using one-way analysis of variance and least significant difference (LSD) methods. The analysis of data was done using SPSS statistical software while graphs were done using EXCEL software. Results and DiscussionThe results revealed that among six plant species, T.aphylla, T. passerinoides, Se.rosmarinus and Pr. juliflora with average survival percentage (in all three regions), 95.8, 91.6, 81.9 and 75.6% respectively, had greatest chance to be present in the adverse environmental conditions of this region. Eu. camaldulensis was able to survive in low salinity (66.6%), even though it failed to survive in high salinity and had a very low survival percentage (6.2%) in medium salinity. Ly.depressum's inability to survive in high and medium salinity and a low survival percentage (27%) in low salinity were reasons why it was not recommended for biological rehabilitation projects in similar ecological conditions. The height and canopy cover of all the studied species, except for Pr. juliflora, had significant differences at different salinity levels. It is recommended to plant native plants, such as T. aphylla, T. passerinoides, and Sei. rosmarinus, in this area and areas with similar ecological conditions, based on the results.